Investigação do mecanismo de ação vasorrelaxante de AAL 195, um inibidor de fosfodiesterase 4, em artéria mesentérica superior de ratos - Silva, Jessyka Carolina Galvão da (2017)
Phosphodiesterases (PDEs) are enzymes that promote hydrolysis of cAMP/cGMP. PDE inhibitors have been useful in the therapy of diseases which are intrinsically related to deregulations in vascular tone by increasing levels of these second messengers. Thus, PDE inhibitors may be important in the treatment of cardiovascular diseases. AAL 195 is a compound synthesized from structural modifications of the molecules of Zardaverina and Rolipram, two PDE4 inhibitors known. Binding assays and molecular modeling showed AAL 195 is a potent and selective inhibitor of these enzymes. Therefore, the aim of this study was to evaluate the vasorelaxant effect of AAL 195 in superior mesenteric artery of rats and elucidate the mechanisms involved in this it. Male Wistar rats (250 – 300g) were euthanized by exsanguination under anesthesia and superior mesenteric artery was removed, cut in rings (2-4 mm), which were mounted in organ baths containing Tyrode's solution at 37°C and gassed with 95% O2 - 5% CO2. For isometric tension recordings, each ring was fixed in a force transducer connected to an acquisition system. The values were expressed as mean ± S.E.M. Data were analyzed using Student's t test or one-way ANOVA, followed by Bonferroni (p<0,05). AAL 195 (10-9 – 10-5 M) induced relaxation rat mesenteric rings pre-contracted with phenylephrine (PHE) in a concentration-dependent manner. After removal of endothelium, the effect wasn’t changed. In preparations without endothelium, KCl 20 mM and tetraethylammonium (TEA) (5 mM) significantly attenuated the concentration-response curve for the AAL 195. After blocking with glibenclamide (GLIB) the concentration-response curve was shifted to the right, without reducing the maximum effect. However, after blocking with 4-aminopyridine (4-AP) or with TEA (1mM) was significantly reduced the efficacy and potency of AAL 195. In rings without endothelium, contracted with KCl 80 mM (3x10-8 – 10-2 M), AAL 195 promoted vasorelaxation concentration-dependent. When comparing the pharmacological parameters between PHE and KCl 80 mM, AAL 195 was more potent after pre-contraction by PHE, without changing the maximum effect. In depolarizing solution nominally without calcium, AAL 195 (3x10-6, 10-5, 3x10-5, 10-3, 3x10-3, 10-2 M) inhibited the cumulative contractions induced by CaCl2. In Ca2+ free medium, pre-incubation with AAL 195 (10-9; 3x10-7; 10-6; 3x10-6; 10-5 M) significantly attenuated the transient contractions induced by phenylephrine (10 μM). In the same experimental conditions, only the concentration of 10-5 M AAL 195 was able to significantly attenuate the contractions induced by 20 mM caffeine. Given the above, it can be concluded AAL 195 promotes vasorelaxant effect in superior mesenteric artery isolated rat, independently of vascular endothelium. Furthermore this effect is non-specific and appear to involve the activation of K+ channels as well as the reduction in intracellular Ca2+ via inhibition of Ca2+ influx and inhibition of Ca2+ mobilization from intracellular stores, mainly by IP3 receptors.